(untitled) (MAUSAM, 2001)
An equilibrium experiment has been conducted with CCM3 climate model in which the amount of CO2 in the model atmosphere is doubled and the differences in resulting climate has been examined. The results show that there is an overall decrease in outgoing longwave radiation indicating the possible increase in cloudiness. The total rainfall may not change significantly but the temporal and spatial distributions over India are likely to change as observed in past long term trends.